Disorganized Labour: Canadian Unions and the Constitution Act - Savage, Larry (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d'études canadiennes, 2007)
AbstractThis article focuses on the Canadian labour movement's experience with constitutional reform in the early 1980s. Specifically, it argues that political divisions within the labour movement and the New Democratic Party (NDP) convinced the leadership of the Canadian Labour Congress (CLC) to exclude itself from the process of patriating the Constitution. Several scholars have previously argued that the CLC was either unaware of or genuinely disinterested in constitutional issues. However, primary sources strongly indicate that these explanations are simply insufficient. Although it is accurate to suggest that the CLC was not an active participant in the process of constitutional reform, inactivity should not be confused with disinterest. The Congress made a strategic political decision to exclude itself from the patriation debate in order to avoid an internal battle between its allies in the NDP and its affiliate, the Québec Federation of Labour. Résumé